EFEKTIVITAS BANTUAN PANGAN NON TUNAI DALAM PENGENTASAN KEMISKINAN DI KELURAHAN PRAWIRODIRJAN GONDOMANAN YOGYAKARTA - Zulianti, Zulianti; Julianti, Julianti (PARADIGMA: Jurnal Ilmu Administrasi, 2023)
The research method used is descriptive qualitative. The types of data in this research are primary data and secondary data. Data collection techniques used are observation, interviews, and documentation. Research result; The Non-Cash Food Assistance Program (BPNT) in the Prawirodirjan Village has not been maximized because it is not on target. The implementation and distribution of the Non-Cash Food Assistance Program to be right on target needs to be re-data collected periodically and routinely. It is necessary to increase the amount of assistance received by beneficiary families so that the BPNT program's goal of reducing the public expenditure burden is achieved.Keyword: Program Effectiveness; Non-Cash Food Assistance Program.